1998
DOI: 10.1080/09629359890811
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory cytokines in newborn infants

Abstract: Serum levels of IL-1beta, IL-6 and TNF-alpha were measured in 48 healthy, termed neonates on the 1st (N1), 5th (N5) and 40th (N40) day after birth, compared with those in maternal serum (MS), umbilical cord (UC) and adult controls. Cytokine values in N1 and N5 were significantly elevated, than those in UC and in controls (P<0.0001). IL-1beta and IL-6 declined significantly from N1 to N40 (P<0.0001), while TNF-alpha increased significantly from N1 to N5 and declined thereafter. MS infinity IL-1beta and IL-6, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
1
4

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 24 publications
1
25
1
4
Order By: Relevance
“…It is possible that its expression may have occurred at earlier phases of tissue injury, or that healthy infants may spontaneously have elevated levels of TNFα early in postnatal life as supported by the previous report of an increase in the first 40 days of life (26). In this context, our findings of increased expression of TNFR1 and TNFR2 mRNA in the livers, as well as increased immune-localization of TNFR2 to intrahepatic cholangiocytes at the time of diagnosis, point to a potential activation of this pathway at the tissue level, perhaps focusing the consequences of TNFα to the hepatobiliary system.…”
Section: Discussionmentioning
confidence: 57%
“…It is possible that its expression may have occurred at earlier phases of tissue injury, or that healthy infants may spontaneously have elevated levels of TNFα early in postnatal life as supported by the previous report of an increase in the first 40 days of life (26). In this context, our findings of increased expression of TNFR1 and TNFR2 mRNA in the livers, as well as increased immune-localization of TNFR2 to intrahepatic cholangiocytes at the time of diagnosis, point to a potential activation of this pathway at the tissue level, perhaps focusing the consequences of TNFα to the hepatobiliary system.…”
Section: Discussionmentioning
confidence: 57%
“…In contrast to lymphocytic cytokines, IL-1␤, IL-6, and TNF-␣ were spontaneously released by blood cells from mothers as well as their neonates (data not shown), likely reflecting the monocytic activation normally associated with pregnancy and delivery (3,37). As shown in Fig.…”
Section: Vol 68 2000mentioning
confidence: 97%
“…The proinfl ammatory cytokine IL-6 concentration in neonates is rapidly decreased time course dependently and other studies in animals have shown that the peak of IL-6 is 6-12 h after hypoxia insults [23] . Thus, it is possible that some cytokine concentrations (IL-6, TNF-␣ , and IFN-␥ ) might be drastically changed time course dependently after birth [23,[34][35][36][37] .…”
Section: Discussionmentioning
confidence: 99%